2002
DOI: 10.1034/j.1398-9995.2002.03366.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial challenges with aerosolized food in asthmatic, food‐allergic children

Abstract: We have presented a prospective series of children with food allergy who developed symptoms of asthma with exposure to aerosolized food allergens. Our data demonstrates that, as in the case of other aeroallergens, inhaled food allergens can produce both early- and late-phase asthmatic responses. This highlights the importance of considering foods as aeroallergens in children with coexistent food allergy and allergic asthma. For these children, dietary avoidance alone may not be sufficient and further environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Data support the idea that exposure to aerosols of food products could lead to food allergy (Leser et al 2001;Roberts et al 2002). Sensitization might occur via dermal, respiratory, or gastrointestinal exposure.…”
Section: Sensitive Populationssupporting
confidence: 50%
“…Data support the idea that exposure to aerosols of food products could lead to food allergy (Leser et al 2001;Roberts et al 2002). Sensitization might occur via dermal, respiratory, or gastrointestinal exposure.…”
Section: Sensitive Populationssupporting
confidence: 50%
“…Roberts et al [ 44 ] recently reported that a group of children with food allergies also developed asthma when exposed to the aerosolized form of the food. Children with IgE-mediated food allergy developed asthma on inhalational exposure to the relevant food allergen while it was being cooked.…”
Section: Other Foods Implicated In Inhalation Reactionsmentioning
confidence: 97%
“…Neither the patient nor the technician making recordings was aware about ingredients of placebo or active test food. A positive challenge was defined as one where symptoms such as wheeze, chest tightness, shortness of breath, coughing, a drop in FEV 1 of at least 15% for asthma (Roberts et al, 2002), and sneezing, runny noses for rhinitis occurred within 1 h of the exposure. Medication and resuscitation equipment were available in the food challenge area in the clinic.…”
Section: Food Challengementioning
confidence: 99%